Analysis of E-Procurement Implementation in Effectiveness Procurement of Goods and Services: (Case Study at PT. KERETA API INDONESIA (PERSERO)) - Hendayani , Ratih; Fauzi, Putri Aulia Fariha (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
The use of technology in the business industry in Indonesia provides opportunities for encouraging the industry to optimize technological developments that are getting better. The industry releases new technology to compete with its competitors. One of the strategies that can be implemented to optimize the supply chain is through the procurement of goods and services (PGS). This technology support allows companies to carry out PGS processes electronically. The research objective of this study is to determine how the relationship system specification, implementation management, governance structure, total acquisition cost, and organization characteristics to e-procurement effectiveness in implementation at PT. Kereta Api Indonesia (Persero). The analysis technique used is descriptive analysis with a quantitative method of multivariate analysis using SEM ( Structural Equation Modeling ), namely Partial Least Square (PLS) with SmartPLS software. The result of this study shows that the variables which have no effect are system specifications with implementation management, implementation management with changes in government structures, changes in government structures with e-procurement effectiveness, organizational characteristics, implementation management can mediate specification system with governance structure, implementation management can mediate specification system with total acquisition cost, implementation management can mediate specification system with organizational characteristics, government structure can mediate implementation management, and organizational characteristics can mediate implementation management with e-procurement effectiveness at PT. Kereta Api Indonesia (Persero). This research recommends PT. Kereta Api Indonesia (Persero) to continue to improve and maintain the e-procurement system so that it can continue to improve systems that facilitate relationships between companies and vendors.